"Oneness through the sharpening of contradictions": Theosophical Polarity in Scriabin's Late Harmonic Practice. Issue 3 (3rd July 2017) - Gawboy, Anna
ABSTRACT: Scriabin used the term "polarity" to describe harmonic relationships based on the tritone. While modern readers may interpret polarity as simple opposition, the Theosophical literature Scriabin read emphasized an older conception of polarity as a mystical paradox in which unity arises out of opposition and vice versa. The esoteric definition of polarity corresponds to recurring concepts in Scriabin's creative philosophy as well as the idiosyncratic behavior of dominant-type sonorities related by tritone in Scriabin's late style.